2020
DOI: 10.1002/bjs.11655
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sentinel node navigation surgery versus laparoscopic gastrectomy with lymph node dissection for early gastric cancer: short-term outcomes of a multicentre randomized controlled trial (SENORITA)

Abstract: Background Sentinel node navigation surgery reduces the extent of gastric and lymph node dissection, and may improve quality of life. The benefit and harm of laparoscopic sentinel node navigation surgery (LSNNS) for early gastric cancer is unknown. The SENORITA (SEntinel Node ORIented Tailored Approach) trial investigated the pathological and surgical outcomes of LSNNS compared with laparoscopic standard gastrectomy (LSG) with lymph node dissection. Methods The SENORITA trial was an investigator‐initiated, ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…In terms of the type of gastrectomy, stomach-preserving surgery that comprised endoscopic submucosal dissection (ESD), endoscopic full-thickness resection, laparoscopic wedge resection, or laparoscopic segmental resection was carried out in 81% of patients in the SN navigation surgery group. There was no significant difference in the rate of postoperative complications between the groups ( 39 ). A primary survival analysis was reported in 2020, showing that 3-year DFS was 95.5% in the standard gastrectomy group and 91.8% in the SN navigation surgery group [hazard ratio (HR)=1.901, 95% confidence interval (95% CI), 0.911−3.967].…”
Section: Navigation Surgery Based On Sn Biopsy For Early Gastric Cancer: History and Current Statusmentioning
confidence: 85%
“…In terms of the type of gastrectomy, stomach-preserving surgery that comprised endoscopic submucosal dissection (ESD), endoscopic full-thickness resection, laparoscopic wedge resection, or laparoscopic segmental resection was carried out in 81% of patients in the SN navigation surgery group. There was no significant difference in the rate of postoperative complications between the groups ( 39 ). A primary survival analysis was reported in 2020, showing that 3-year DFS was 95.5% in the standard gastrectomy group and 91.8% in the SN navigation surgery group [hazard ratio (HR)=1.901, 95% confidence interval (95% CI), 0.911−3.967].…”
Section: Navigation Surgery Based On Sn Biopsy For Early Gastric Cancer: History and Current Statusmentioning
confidence: 85%
“…The dual-tracer method (ICG and radiolabeled human serum albumin) is been used for LSNNS. Short-term surgical outcomes revealed a comparable rate and severity of postoperative complications between the groups, indicating that LSNNS is feasible and safe [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Korea, a phase III RCT, the SENORITA trial, which compared laparoscopic SNNS to conventional gastrectomy with the primary endpoint of 3‐year disease‐free survival (DFS), showed comparable morbidity and mortality rates between the two groups. However, SNNS failed to show non‐inferiority because more recurrence (mainly metachronous gastric cancer) was seen in SNNS (SNNS vs conventional: 91.8% vs 95.5%; HR, 1.901; 95% CI, 0.911‐3.967 [non‐inferiority margin: 2.737]) 15,16 . However, they concluded that SNNS could be an alternative if rescue surgery is appropriately performed; this was supported by 3‐year overall survival (OS) and disease‐specific survival that were equivalent to those of conventional surgery.…”
Section: Surgical Management Of Gastric Cancermentioning
confidence: 99%